Studies on Ottoman Ambassadors and Embassies in the Republican Era - Hacer Topaktaş Üstüner (Tarih Dergisi)
This article, which evaluates the studies on Ottoman ambassadors and embassies during the Republic period, discusses the requirements, possibilities, problems of research in this field and the general status of the published works. The article argues that, during the Republican period, a considerable amount of work was carried out on Ottoman ambassadors and embassies, which were the most important actors in the relations with foreign states throughout the long history of the Ottoman Empire, but there are still many topics waiting to be researched. The article suggests that the sources and publications related to the Ottoman ambassadors, especially in the European context, are increasing, and this paves the way for a broader perspective on Ottoman foreign policy and diplomacy. At the same time, the article provides a general literature list by touching on the leading studies in this field.